TARGETED ADVERTISING ON SOCIAL NETWORKS: ITS POPULARITY AND EFFICIENCY - Hrynkevych , S.S.; Sorokina , Z.D.; Sitarchuk , M.A. (The actual problems of regional economy development, 2021)
The aim of the article is to study the popularity and effectiveness of targeted advertising as a tool of marketing communications. To achieve this goal used a set of methods: theoretical - analysis, synthesis and systematization of scientific literature on the use of targeted advertising as a tool of marketing communications - to clarify the current state of research, the availability of platforms for targeting in social networks, types of targeted advertising; empirical - conversation, observation, survey - to find out the basic skills and competencies of a modern targetologist, necessary in professional activities. The information base of this research consisted of works of domestic and foreign scientists, statistics, data of web analysts, experts. The popularity and effectiveness of targeted advertising on social networks has been proven. The basic requirements for the skills and competencies of a targetologist are formed, namely the ability to conduct marketing analysis, write texts that "sell", work in graphics and video editors, in web analytics systems. Targeted advertising by types is characterized and systematized, in particular, the main types include: behavioral targeting (audience targeting), contextual targeting, search retargeting, site retargeting, predictive targeting, demographic and also, geographical targeting. The effectiveness of targeted advertising on social networks was evaluated and social networks were analyzed as the main platforms for launching targeted advertising (Facebook, Instagram, Twitter, Viber, Telegram, Tik Tok, QQ, WeChat, Tumblr, Sina Weibo). The main platforms for targeting on social networks - Facebook and Instagram - are outlined. Examples of the use of targeted advertising by the retail network Sephora, Tesco and the charity fund "Amanda" are given. The scientific novelty of the obtained results lies in the formation of the basic skills and competencies of a modern targetologist. The results of the study can be used in the training of target specialists and in organizing the process of preparation for the launch of targeted advertising.